Уравнения √3 + 4x + 4x2 · arctg(2x + 1) + √6 - 4x + x2 · arctg(2 - x) = 0.

Маришка1231 Маришка1231    3   08.10.2019 03:50    1

Ответы
анна2248 анна2248  08.10.2019 03:50

√3 + 4x + 4x2 · arctg(2x + 1) + √6 - 4x + x2 · arctg(2 - x) = 0

4x2 + 4x + 3 = (2x + 1)2 + 2; x2 - 4x + 6 = (x - 2)2 + 2

√2 + (2x + 1)2 · arctg(2x + 1) = √2 + (х - 2)2 · arctg(х - 2)

f(t) = √2 + t2 · arctgt нечетная возрастает на r

f(2x + 1) =
f(x - 2) выполнено, если   2х + 1 = х - 2

отсюда x=-3

ответ: x=-3

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика